(untitled) (Harmoni, 2014)
The perceived differences between Shiites and Sunnis often causes disharmony in the relationship between the two. The severity of this disharmony is expressed in the form of expiation (takf├«r) and even violence between the two groups. Whereas the difference between a man of grace, if not motivated and caused by the attitudes and actions of fanaticism of school or flow (altaΓÇÿ ashshub), and selfishness or lust (ittib├óΓÇÿ al-haw├ó). To that end, efforts towards the harmonization of these two major schools has become important, and can even be seen as a political and social necessity (dar├╗rah siy├ósiyyah wa-hatmiyyah w├óqiΓÇÿiyyah). One such harmonization effort is done through us├╗l al-fiqh. In this context, the concept of ijtih├ód were revitalized and re-actualized in order to be relevant and important. The application of ijtih├ód as a medium for the harmonization of Shia and Sunni relations must be placed within the framework of the tashw├«b paradigm and not the takhth├« paradigm.